The complete mitochondrial genome and phylogenetic analysis of White-bellied Heron Ardea insignis (Pelecaniformes：Ardeidae) - Duan, Yubao (Mitochondrial DNA B Resour, 2018)
The White-bellied Heron Ardea insignis is Critically Endangered wading bird. In this study, we first sequenced and described the complete mitochondrial genome and phylogeny of A. insignis. The whole genome of A. insignis was 18,656 bp in length and contained 14 protein-coding genes, 23 transfer RNA genes, two ribosome RNA genes, and two non-coding control regions. The overall base composition of the mitochondrial DNA was 30.86% for A, 24.60% for T, 30.48% for C, and 14.05% for G, with a GC content of 44.54%. A phylogenetic tree confirmed that A. insignis belonged to genus Ardea, family Ardeidae, and was sister to A. purpurea. This information will be useful in the current understanding of the phylogeny and evolution of Pelecaniformes.